Nilai Ekonomis Garam dan Kesejahteraan Petani Garam di Kecamatan Tlanakan Kabupaten Pamekasan - Firman Iswahyudi Mustafa; Titien Sulistiawaty; Luluk latifah (Ekopem: Jurnal Ekonomi Pembangunan, 2021)
This study aims to determine the factors that influence the economic value of salt and to determine the effect of fluctuations in the economic value of salt on the welfare of salt farmers. This research is a qualitative research, which is a research that is used to determine the economic value factor of salt that occurs in Tlanakan District, Pamekasan Regency. The population in this study were all members of Salt farmers in Tlanakan District. The data analysis technique in this study used a process of systematically searching and compiling data obtained from interviews, field notes, and documentation. The conclusion of this study shows that imports are the biggest influence on the economic value of local salt, as a result if imports continue, local salt cannot reach the price desired by local people. Fluctuations in the economic value of salt greatly affect the welfare of farmers in meeting the needs and desires of their families.